PENGENALAN COLLABORA OFFICE UNTUK PELAJAR SMK IT MATHLA’UL ANWAR SEGARAN - Ma'ruf Ali Fitri; Tin Hartini; Yudha Asmara (Universitas Islam 45 Bekasi, 2022)
Technology keeps advancing with time. Right now, most modern people use computers. That's including administration work. Office suites are a bundle of computer’s application used for administration work. What's used most in office suites are word processors and spreadsheets. The most used office suites are Microsoft Office. But unfortunately Microsoft Office is a paid application, and there are a lot of people who use this application illegally. LibreOffice is one of the alternatives for Microsoft Office. This application is an open source application. Which means this application has its source code spread on the internet and anyone is allowed not only to use this application but also modify it according to their needs. Collabora Office is one of the applications that use LibreOffice's source code as its basis. One of Collabora Office's superiority over LibreOffice is that this application can run on more operating systems and devices compared to LibreOffice. That’s the reason Collabora Office was introduced in this community service. This activity is done by way of training where there is presentation and demonstration. After this activity has been done, students show an increase in skills of both word processor and spreadsheets application. Where the error in word processor is reduced by 1.85%, and uses of basic function on spreadsheets. I hope, the next community service can introduce open source based applications.